Ceremonial tobacco use in the Andes: Implications for smoking prevention among indigenous youth - Alderete, Ethel del Carmen (2010)
The purpose of this study was to identify Andean youth's beliefs regarding ceremonial tobacco use and to discuss potential applications of findings in tobacco control interventions. The study was conducted in the Province of Jujuy, Argentina among 202 boys and girls, 10 to 20 years of age, living in rural and urban areas. The world of beliefs and meanings became accessible by asking youth to focus on tangible experiences regarding the Pachamama ceremony, a ritual honoring Mother Earth. Concepts such as reciprocity, the unity of material and spiritual realms, and the complementary nature of opposite forces were linked to beliefs about ceremonial tobacco use. Three domains for understanding smoking behaviour beliefs and norms were identified including mechanisms of production, conceptual tenants and behavioural expressions. These findings suggest that tobacco control interventions based on solidarity, reciprocity, and non-rational ways of learning are more culturally appropriate for native populations in the Andes than the current individual behaviour change models and have the potential applications with other indigenous populations. The research methods also have the potential for generalized application in cross-cultural studies of health behaviours in understudied populations in middle and low-income countries.